2022
DOI: 10.1089/mdr.2020.0339
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Multidrug-Resistant ST58 Escherichia coli Harboring Extended-Spectrum Beta-Lactamase of the CTX-M-1 Class in a Fecal Sample of a Captive Baird's Tapir (Tapirus bairdii) in Costa Rica, Central America

Abstract: This study's main objective was to analyze the antibiotic susceptibility profile of Escherichia coli isolates obtained from a fecal sample of a captive Baird's tapir (Tapirus bairdii) in Costa Rica. Materials and Methods: The fecal sample was collected inside the enclosure on March 3, 2017, right after the animal defecated. Samples were cultured on MacConkey agar plates nonsupplemented and supplemented with 2 mg/mL of cefotaxime. Bacterial identification and antibiotic susceptibility were performed with the Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Following the current scientific opinion, Brisson et al (63) reported a higher probability of carrying antimicrobial-resistant E. coli for African herbivores kept in zoos than those of the same species sampled in natural parks. By non-cultural methods, apes in captivity showed more ARGs than their counterparts in wild environments (64). Such observations agree with previous observations in Costa Rica for the Central American tapir (Baird's tapir; Tapirus bairdii).…”
Section: Discussionsupporting
confidence: 90%
“…Following the current scientific opinion, Brisson et al (63) reported a higher probability of carrying antimicrobial-resistant E. coli for African herbivores kept in zoos than those of the same species sampled in natural parks. By non-cultural methods, apes in captivity showed more ARGs than their counterparts in wild environments (64). Such observations agree with previous observations in Costa Rica for the Central American tapir (Baird's tapir; Tapirus bairdii).…”
Section: Discussionsupporting
confidence: 90%
“…55,56 Previously, E. coli ST58 harboring multiple antimicrobial resistance and virulence genes have been reported in store-bought fresh produce as well as from pork sausage in Germany, 57,58 similar to the results from the current study. Although limited information is available about the ST58 serotypes detected in the current 59 In foodproducing environments, E. coli is often used to indicate fecal contamination as it appears at low background levels in the environment but has high survival rates. 60 Furthermore, the WHO reported that ESBL-producing E. coli should be used as an indicator in monitoring programs to facilitate the establishment of integrated multisectoral antimicrobial resistance surveillance in One Health.…”
Section: ■ Discussionmentioning
confidence: 99%
“…coli strains have caused human extraintestinal infections, including sepsis, and are reported as one of the main ESBL-producing E. coli circulating in the human–animal–environment . In food-producing environments, E.…”
Section: Discussionmentioning
confidence: 99%